1989
DOI: 10.1002/jez.1402520108
|View full text |Cite
|
Sign up to set email alerts
|

Effects of magnetic resonance imaging (MRI) on the formation of mouse dentin and bone

Abstract: The effects of magnetic resonance imaging (MRI) on dentin and bone formation in mice were examined using standard autoradiographic and liquid scintillation procedures. It was observed that exposure to a standard 23.2 min clinical multislice MRI (0.15T) procedure caused a significant increase in the synthesis of the collagenous matrix of dentin in the incisors of mice. There were no significant effects on alveolar and tibial bone matrix synthesis. These results suggest that the magnetic fields associated with M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Prato et al (1990Prato et al ( , 1994) discovered a significant increase in the permeability of the blood brain barrier. Kwong-Hing et al (1989) examined the acute exposure effects of a 0.05 T MRI on dentin and bone formation in mice. They found that the exposure caused a significant increase in the synthesis of the collageneous matrix of dentin in the incisors.…”
Section: Introductionmentioning
confidence: 99%
“…Prato et al (1990Prato et al ( , 1994) discovered a significant increase in the permeability of the blood brain barrier. Kwong-Hing et al (1989) examined the acute exposure effects of a 0.05 T MRI on dentin and bone formation in mice. They found that the exposure caused a significant increase in the synthesis of the collageneous matrix of dentin in the incisors.…”
Section: Introductionmentioning
confidence: 99%